2004
DOI: 10.1590/s1519-38292004000400011
|View full text |Cite
|
Sign up to set email alerts
|

Principais causas básicas da mortalidade infantil no Distrito Federal, Brasil: 1990 a 2000

Abstract: Objectives: to characterize the tendency of infant mortality in Distrito Federal (DF) considering underlying causes of death and the avoidable causes criteria between 1990 and 2000.Methods: an ecological study using total infant deaths and births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Non-preventable deaths corresponded to 19.2% of the total and were related to either congenital malformations incompatible with life or birth weight lower than 1,000 g. Adequate pregnancy monitoring could have reduced 11.5% of the deaths, and adequate delivery care, 5.1% 16 , 17 . In a study performed in the Brazilian Federal District in 1999 and 2000, classifying death according to preventability, Monteiro and Schmitz 18 have reported a similar result, with 35.5% of deaths being reducible by means of prevention, diagnosis and early treatment actions 18 . In a study carried out from 2000 to 2003 in the city of Porto Alegre, where 1,139 deaths occurred, Jobim and Aerts 15 reported that 76.6% were classified as preventable.…”
Section: Discussionmentioning
confidence: 87%
“…Non-preventable deaths corresponded to 19.2% of the total and were related to either congenital malformations incompatible with life or birth weight lower than 1,000 g. Adequate pregnancy monitoring could have reduced 11.5% of the deaths, and adequate delivery care, 5.1% 16 , 17 . In a study performed in the Brazilian Federal District in 1999 and 2000, classifying death according to preventability, Monteiro and Schmitz 18 have reported a similar result, with 35.5% of deaths being reducible by means of prevention, diagnosis and early treatment actions 18 . In a study carried out from 2000 to 2003 in the city of Porto Alegre, where 1,139 deaths occurred, Jobim and Aerts 15 reported that 76.6% were classified as preventable.…”
Section: Discussionmentioning
confidence: 87%
“…Of the causes, infec ous parasite-borne diseases showed a decrease of 84.2%, followed by respiratory diseases and malnutri on (7) . In another analysis from the same state, the Infant Mortality rate (IMR) of all the components underwent a reduc on, although in the poorer regions these were s ll high when compared to those in regions with be er economic condi ons (19) .…”
Section: The Center-west Regionmentioning
confidence: 99%
“…Of these, 71.4% had been published in Public Health periodicals (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and 14.8% in Nursing periodicals (24)(25)(26)(27)(28)(29)(30)(31) .…”
Section: Scien Fi C Produc On In Post-neonatal Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, o conhecimento do perfil de morbidade e mortalidade de ambos os grupos é essencial para o planejamento das ações na área da saúde. 1,2 As afecções perinatais não só constituem a primeira causa de mortalidade neonatal no país, como também interferem nas mortes ao longo do primeiro ano de vida. 1,2 Já a ocorrência de morbidade grave e de morte materna está diretamente relacionada à adequada atenção durante o ciclo gravídico-puerperal, podendo ser significativamente reduzidas se a assistência profissional e a estrutura institucional forem adequadas, independentemente de outras características.…”
Section: Introductionunclassified